Evaluating the Effectiveness of Professional Development Programs on Improving Teaching Quality in Chinese Universities (Journal of Interdisciplinary Insights, 2024)
This study evaluates the effectiveness of professional development (PD) programs in enhancing teaching quality within Chinese universities, focusing on Shandong University, Qingdao University, and Shandong Normal University. Drawing on a quantitative approach, data was collected from 360 faculty members through structured questionnaires. Descriptive statistics revealed a balanced gender distribution, with mid-career and senior-level teaching staff represented. The majority had 6-10 years of teaching experience. Faculty members perceived PD programs positively, reporting high mean scores for effectiveness and satisfaction. Inferential statistics indicated significant correlations between participation in PD programs and improvements in teaching methods, subject knowledge, and classroom management. Comparative analysis showed no significant differences in perceptions across the universities, suggesting consistent effectiveness. This study underscores the importance of continuous faculty development and the potential for scaling effective PD initiatives in Chinese higher education.